Advances in Bioinformatics and Computational Biology 7th Brazilian Symposium on Bioinformatics, BSB 2012, Campo Grande, Brazil, August 15-17, 2012. Proceedings - Souto, Marcilio C.; Kann, Maricel G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 7th Brazilian Symposium on Bioinformatics, BSB 2012, held in Campo Grande, Brazil, in August 2012. The 16 regular papers presented were carefully reviewed and selected for inclusion in this book. It also contains a joint paper from two of the guest speakers. The Brazilian Symposium on Bioinformatics covers all aspects of bioinformatics and computational biology, including sequence analysis; motifs, and pattern matching; biological databases, data management, data integration, and data mining; biomedical text mining; structural, comparative, and functional genomics; personal genomics; protein structure, modeling, and simulation; gene identification, regulation and expression analysis; gene and protein interaction and networks; molecular docking; molecular evolution and phylogenetics; computational systems biology; computational proteomics; statistical analysis of molecular sequences; algorithms for problems in computational biology; applications in molecular biology, biochemistry, genetics, medicine, microbiology and associated subjects.
Keywords: Computer science; Computer software; Database management; Artificial intelligence; Optical pattern recognition; Bioinformatics; Computer Science; Artificial Intelligence (incl. Robotics).; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Database Management; Computational Biology/Bioinformatics.; Pattern Recognition